Inheritance expectations and social isolation: evidence from South Korea - Saade, Ahmed J.; Alexiou, Constantinos; Belghitar, Yacine (https://www.kci.go.kr/kciportal/landing/article.kci?arti_id=ART003140504, 2024)
Little is known about the economic causes of social isolation among elders in spite of the phenomenon becoming a growing policy concern in many developed countries with ageing populations. This paper fills this gap by assessing the role of inheritance as a novel determinant of social isolation among elders. Drawing on bequest motive theory as well as aspirations theory, we utilize a granular dataset from South Korea spanning the period 2008 – 2020. The nascent evidence suggests that adult children having high inheritance expectations is beneficial to parents. In particular, having higher inheritance expectations is found to increase the frequency of parent-child meetings, thus lowering the risk of parents’ isolation. Additionally, mothers who report a higher likelihood of leaving an inheritance to their children are less isolated and disclose better well-being. Lastly, we find that the split of inheritance following a father’s death has consequences on the subsequent isolation of mothers. To the best of our knowledge this is the first study that investigates the direct role of inheritance in the creation of elderly social isolation, hence providing useful insights to policymakers of countries facing this problem.
Keywords: Ageing; Aspirations; Inheritance; Loneliness; Social isolation; Strategic Bequest